Rancang Bangun Teaching Aid Motor Servo AC R88M Berbasis PLC NX1P2 Sebagai Alat Bantu Pengajaran - Castrena Abadi, Sarosa; Rokhim, Ismail; Wiyono, Andri; Rahmah, Mustika (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2023)
Teaching aids are used in the field of education to streamline the implementation of the learning process. In this research, AC servo motor learning media with type R88M-1M10030-S2. The learning media will focus on controlling the position and speed of the servo motor for the x, y and z axes. This research uses the experimental work method. Testing of this research is carried out in Motion Variety parameter testing, NC function testing, HMI function testing, and user evaluation testing. It was found that the percentage of deviation value was 4.9%. In position testing, the deviation value of the X and Z axes has a small average final error with an X-axis error value of 0.21% and a Z-axis of 0.24%. It can be seen that the average Y-axis error is the largest with an average error value of 5.84%. Overall the average value of the HMI evaluation is 89% for the quality of the AC Servo Motor Teaching Aid HMI that has been made. This figure is classified as very good to continue using the tool as an auxiliary medium for the teaching process.